2003
DOI: 10.1159/000069274
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavone Consumption Does Not Increase the Bone Mass in Osteopenic Obese Female Zucker Rats

Abstract: Some controversy exists in the literature concerning the effects of leptin on bone metabolism. Thus we have compared femoral bone density and biochemical markers of bone metabolism in male and female fatty (leptin-resistant) Zucker rats and their lean homozygous controls at 3 and 6 months of age. At 3 months, no differences concerning total, diaphyseal (cortical bone), and distal metaphyseal (trabecular bone) femoral bone densities, plasma osteocalcin concentrations, and urinary deoxypyridinoline excretion wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…In addition, the ZDF rats excreted urinary calcium at high levels compared to lean rats. More recently, Picherit et al (2003) reported that, at 24 weeks of age, the total, diaphyseal, and metaphyseal femoral bone densities of ZDF rats were significantly lower than those of littermate lean rats while in 12-week old animals, these parameters were no different in the two groups. Similarly, serum osteocalcin levels were lower in the ZDF rats than in lean controls at both 12 and 24 weeks of age, but the difference was statistically significant only in 24-week-old animals.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, the ZDF rats excreted urinary calcium at high levels compared to lean rats. More recently, Picherit et al (2003) reported that, at 24 weeks of age, the total, diaphyseal, and metaphyseal femoral bone densities of ZDF rats were significantly lower than those of littermate lean rats while in 12-week old animals, these parameters were no different in the two groups. Similarly, serum osteocalcin levels were lower in the ZDF rats than in lean controls at both 12 and 24 weeks of age, but the difference was statistically significant only in 24-week-old animals.…”
Section: Discussionmentioning
confidence: 96%
“…All male ZDF rats develop obesity, hyperleptinemia, hyperglycemia, hyperinsulinemia, and insulin resistance when fed a rodent diet of Purina 5008. Recent studies have shown that many diabetic complications are found in ZDF rats, including periodontal disease (Ryan et al 1999) and diabetic osteopenia (Shibata et al 2000, Picherit et al 2003.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to studies on mice, obese fa/fa rats, which have a mutated leptin receptor, are reported to have a decreased bone mass (Foldes et al 1992, Picherit et al 2003. Models in which leptin has been administered centrally via an i.c.v route have shown a reduced bone mass (Ducy et al 2000, Takeda et al 2002, Elefteriou et al 2004.…”
Section: Discussionmentioning
confidence: 98%
“…Lower femoral BMD and osteocalcin (a marker of bone formation) serum were described in fa/fa rats, as well as decreased trabecular bone volume, trabecular thickness and trabecular number, as measured both by micro-CT and histomorphometry. Picherit et al have compared femoral bone density and biochemical markers of bone metabolism in male and female fatty (leptin-resistant) Zucker rats and their lean homozygous controls at 3 and 6 months of age [39]. Tamasi et al used female leptin receptor-deficient Zucker (fa/fa) rats and their homozygous (Fa/Fa) and heterozygous (Fa/fa) lean controls at 9 and 15 weeks of age.…”
Section: Arbeiten Originalmentioning
confidence: 99%